LANDSCAPE MAP OF VESLOVSKYY PENINSULA (KUNASHIR ISLAND, KURIL ISLAND) - Грищенко, М. Ю.; Карпачевский, А. М.; Леонова, Г. М. (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2015)
Currently, high-scale field surveys-based thematic mapping is not very widespread, though it provides detailed and accurate information about the study area, presented in representative cartographic form. In this paper, authors present the technique of Veslovsky peninsula landscape map composition (Kunashir island, Kuril islands) based on wide field surveys. Veslovsky peninsula is located in the buffer zone of the Kuril nature reserve. The scale of the map is 1:10 000. The map provides detailed information on the topography, vegetation and soil cover of the study area.